Characteristics of Preeclampsia Patients at Central Mamuju Regional Hospital from 2024 to 2025 - Ria Ristiana; Andy Wiraputra (Sean Institute, 2025)
Background: Preeclampsia is a clinical syndrome during pregnancy (after 20 weeks of gestation) characterized by increased blood pressure (>140/90 mmHg) in women whose blood pressure was normal before 20 weeks of gestation. Severe preeclampsia (PEB) is a clinical syndrome during pregnancy (after 20 weeks of gestation) characterized by increased blood pressure (>160/110 mmHg) in women whose blood pressure was normal before 20 weeks of gestation. Risk factors for preeclampsia are age, nulliparity, history of previous preeclampsia, history of hypertension and diabetes mellitus, family history and obesity.Preeclampsia is the leading cause of maternal and infant mortality in Indonesia. Research purposes: This study aimed to determine the characteristics of preeclampsia patients at Mamuju Tengah Regional Hospital from 2024 to 2025. This study used an analytical design with a retrospective cross-sectional approach. This study was conducted using secondary data in the form of patient medical records, then the data was processed using SPSS. Results: From 100 samples, the number of severe preeclampsia cases was 93, preeclampsia cases 6 and eclampsia cases 1.The largest proportion of cases, both in total and in cases of severe preeclampsia, occurred in the 20-35 year age group. The majority of patients were multigravida, namely 86 people (86.0%). Only 14 people (14.0%) were primigravida. The distribution of nutritional status in 100 preeclampsia patients (referring to the total sample) showed that the majority of patients had obesity 2 nutritional status (56 people or 56.0%). Followed by obesity 1 (37 people or 37.0%), overweight (6 people or 6.0%), and only 1 person (1.0%) had normal nutritional status. Most preeclampsia patients (99 people or 99.0%) had no previous medical history. Only 1 person (1.0%) had a medical history. Conclusion: Most cases of preeclampsia, severe preeclampsia, and eclampsia occurred in pregnant women in the productive age group of 20-35 years, and most were multigravida. The most significant finding was a very strong association between the incidence of preeclampsia and obesity nutritional status (reaching 93.0% of the total cases), and most patients had no history of previous comorbidities.